Functionalization of Graphene Oxide with Polysilicone: Synthesis, Characterization and Fire Retardancy in Thiol-Ene Systems. Issue 5 (7th April 2021) - Wu, Fangyi; Bao, Xiaohui; Xu, Huan; Kong, Delong; Wang, Jiangbo
Abstract: Functionalized graphene nanosheets (GO-PA) were synthesized by a facile covalent grafting of graphene oxide (GO) with polyaminosilicone (PA). The structure and morphology of GO-PA were characterized by various measurements. In order to compare the effects of adding GO and GO-PA to thiol-ene (TE), TE/GO and TE/GO-PA nanocomposites were prepared and their fire retardancies were evaluated. The results revealed that the addition of both GO and GO-PA could improve the fire retardancy and residual char of TE nanocomposites, but GO-PA performed much better than GO. Compared with pure TE, the peak heat release rate of the TE/GO-PA nanocomposite was decreased by 31.9% and its residual char was increased from 1.16 to 2.50 wt%. Furthermore, dynamic mechanical thermal analysis showed that the grafting of GO with PA improved the dispersion of the GO sheets in the TE matrix.